FORECASTING FINANCIAL INCLUSION AND ITS IMPACTS ON POVERTY AND INEQUALITY: A COMPARATIVE STUDY IN ASEAN- 5 - Setyo Tri Wahyudi; Rihana Sofie Nabella; Nurul Badriyah; Kartika Sari; Rade (Jurnal Ekonomi Kuantitatif Terapan, 2024)
Financial inclusion has played a vital role in eradicating poverty and inequality in somedeveloping countries over the last few decades. In ASEAN, the growth of financial inclusion is sorapid that it reaches every element of society. Therefore, the purpose of this study is to examineforecasts of financial inclusion, poverty, and inequality in ASEAN. In addition, the study alsoanalyzes the correlation between financial inclusion, poverty, and inequality in ASEAN. Thestudy uses the ARIMA and GMM models for the study period from 2000 to 2022. Projectionsshow that most ASEAN countries have experienced an increase in the long-term financialinclusion index, with Thailand leading the ranking, followed by Malaysia. However, the role offinancial inclusion in poverty does not seem to be so significant in the short term, most likely dueto the still-difficult access for low-income groups.